An investigation of the views and practices of Australian community pharmacists on pain and fever management and clinical guidelines - Mishriky J; Stupans I; Chan V (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Fever and pain are common conditions in the Australian healthcare setting. Whilst clinical guidelines provide important therapeutic recommendations, evidence suggests they are not always followed. Given that community pharmacy is one of the most frequently accessed primary healthcare services, it is important to understand the views and practices of community pharmacists in pain and fever. Objectives: To investigate the views and practices of Australian community pharmacists in pain and fever management, and their views on relevant clinical guidelines. Methods: A cross-sectional study of community pharmacists in Australia was conducted using a customised, anonymous, self-administered, online questionnaire between March and May 2018. To capture a broad range of demographics, pharmacists were recruited via local industry contacts and the Pharmaceutical Society newsletter, with further recruitment through snowball sampling. The main outcomes measured were pharmacists' views, practices and treatment recommendation of choice in pain and fever management, as well as views on clinical guidelines and training. Results: A total of 113 pharmacists completed the survey. In general, paracetamol (72%) was preferred as a recommendation over ibuprofen, and was the drug of choice for most mild to moderate pain and fever scenarios. Majority of pharmacists reported good knowledge of pain and fever management, however, only approximately half reported recent pain management training. Greater than 87% of pharmacists believe that clinical guidelines are useful in fever management, and 79% of pharmacists believe that following clinical guidelines is important in pain management. Conclusions: While most pharmacists recognise the importance of guidelines and demonstrated good pain and fever management, results suggests opportunities to promote additional education, upskilling, and research in this space to further optimise pain and fever management in the community.